2015
DOI: 10.1186/s12870-015-0535-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature stress on the early vegetative development of Brassica oleracea L.

Abstract: BackgroundDue to its biennual life cycle Brassica oleracea is especially exposed to seasonal changes in temperature that could limit its growth and fitness. Thermal stress could limit plant growth, leaf development and photosynthesis. We evaluated the performance of two local populations of B. oleracea: one population of cabbage (B. oleracea capitata group) and one population of kale (B. oleracea acephala group) under limiting low and high temperatures.ResultsThere were differences between crops and how they r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 41 publications
3
68
0
3
Order By: Relevance
“…Plants act in response to different abiotic stresses by shifting and changing concentration of metabolite related to different biochemical pathways so that they can acclimatize to unfavorable physiological changes (Kumar et al, 2012). Heat stress produces a significant reduction in fresh weight and RWC in aerial parts of plants (Rodríguez et al, 2015). In this study, FW and RWC gradually reduced with an increase in temperature in all four wheat cultivars and heat susceptibility index was calculated using these two parameters.…”
Section: Discussionmentioning
confidence: 86%
“…Plants act in response to different abiotic stresses by shifting and changing concentration of metabolite related to different biochemical pathways so that they can acclimatize to unfavorable physiological changes (Kumar et al, 2012). Heat stress produces a significant reduction in fresh weight and RWC in aerial parts of plants (Rodríguez et al, 2015). In this study, FW and RWC gradually reduced with an increase in temperature in all four wheat cultivars and heat susceptibility index was calculated using these two parameters.…”
Section: Discussionmentioning
confidence: 86%
“…Lettuce is a cool season crop with a preferred temperature range of 7-24 • C. Inflorescence initiation is encouraged by exposure to high temperatures and photoperiods of ≥13 h [23]. Producing lettuce above these thresholds affects plasma membrane fluidity, microtubules and microfilaments, and the photosynthetic apparatus [24]. This causes an intracellular signal cascade that ultimately reduces plant yield and quality.…”
Section: Discussionmentioning
confidence: 99%
“…Information on the photosynthetic aspects of brassicas, even as monocrops, is scarce. Important among the related works is that of Rodriguez et al (2015), who found stomatal conductance (gs) varying from 0.2 to 0.8 mol H 2 O m -2 s -1 in kale plants grown under temperatures of 12°C and 32°C respectively. For canola (B. napus L.), Jensen et al (1996) observed an average photosynthetic rate of 29 µmol CO 2 m -2 s -1 , stomatal conductance of between 1 and 1.5 mol H 2 O m -2 s -1 1, and Ci/Ca of 0.82 in plants subjected to a temperature of 22°C.…”
Section: Physiological Performance Of Kalementioning
confidence: 99%
“…The species, Brassica oleracea L., originally domesticated in the coastal region of the Mediterranean, today presents botanical varieties, grown around the world, which adapt to a wide range of climatic conditions (Rodriguez et al, 2015). Among these varieties, kale (B. oleracea L. var.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation